Lactic Acid Bacteria Isolates and the Microbiome of Cincalok, Tempoyak, and Mandai: A Traditional Fermented Food from Kalimantan Island, Indonesia - Retno Murwani; Refa Anggraeni; Gregorius Nico Adi Setiawan; Putri Dyah Astari; Ni Kadek Dita Cahyani; Mada Triandala Sibero; Ambariyanto Ambariyanto (International Journal of Food Science)
Indonesia has abundant traditional fermented food with various lactic acid bacteria (LAB), which can be developed into probiotics for pharmaceutical and functional food and feed products. This research is aimed at (1) obtaining and identifying LAB isolates and (2) studying the microbiome (bacterial diversity and abundance) of spontaneously-fermented traditional foods of Kalimantan Island, Cincalok, Tempoyak, and Mandai. To obtain LAB isolates, food samples were serially diluted and inoculated on MRS agar that contained 1% CaCO3 (MRSA). Isolates forming clear zones were purified and identified by DNA barcoding. The microbiome was studied using genomic-sequencing techniques and analysed for taxonomic composition. Seven pure isolates were obtained from Cincalok, two Tempoyak, and one Mandai. DNA barcoding revealed that the Cincalok seven isolates were Staphylococcus carnosus (strain HSP-S16), Tetragenococcus halophilus (FSB201), Corynebacterium phoceense, Vagococcus vulneris (SS1995), Enterococcus faecalis (S11-6), Pisciglobus halotolerans (C01), and Priestia filamentosa (P3.1); two from Tempoyak, Levilactobacillus brevis (E1D3BL1) and Lactiplantibacillus plantarum (UMCC-2996); and one from Mandai, Staphylococcus cohnii (XAAS.x13; non-LAB). The T. halophilus, E. faecalis, P. halotolerans, L. brevis, and L. plantarum belong to LAB. The P. halotolerans from Cincalok and non-LAB in these three fermented foods were the first documented report. The microbiome revealed the dominance of Firmicutes phyla in the fermented foods, with 93% in Cincalok, 89.94% in Tempoyak, and 60.32% in Mandai. On the genus level, Cincalok was dominated by Tetragenococcus 40.33%, Anaerococcus 23.29%, Vagococcus 9.27%, and Lactobacillus 6.84%. Meanwhile, Tempoyak was dominated only by Lactobacillus 89.94%. Mandai were dominated by Lactobacillus 31.97%, Proteus 17.14%, Aerococcus 16.85%, Mangrovibacter 15.15%, and Vagococcus 6.2%. However, Mandai’s microbiome LAB was not culturable/isolated on MRSA. The plausibility is that those unculturable LAB require coculturing with other bacteria and additional media components to grow on MRSA. This study is the first report regarding the microbiome of Cincalok, Tempoyak, and Mandai, along with their culturable LAB isolates.